PENGEMBANGAN MEDIA PEMBELAJARAN FLIPBOOK DIGITAL GUNA MENUNJANG PROSES PEMBELAJARAN DI ERA REVOLUSI INDUSTRI 4.0 - Muhammad Abror Amanullah (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2020)
Need for innovation in learning is absolutely necessary in the face of the era of digital progress or can be called the industrial revolution 4.0. digital learning intend to present a new situation and atmosphere in learning to students, because conventional learning is not in accordance with the current learning situation of students. The method used in this scientific work is a literature study that is relevant discussion on this scientific work. Learning using flipbook digital is an alternative solution to support student learning in the era of industrial revolution 4.0. learning will be very varied and interesting in terms of visual and audiovisual appearance. So that the use of flipbook digital learning media is a smart solution to present an atmosphere of learning in the classroom that is more interesting, communicative, interactive and supports students' understanding of the material that has been delivered by the teacher.